BDNF levels and liver stiffness in subjects with alcohol use disorder: Evaluation after alcohol withdrawal. (4th March 2021) - Girard, Murielle; Carrier, Paul; Loustaud-Ratti, Véronique; Nubukpo, Philippe
ABSTRACT: Background : Brain-derived neurotrophic factor (BDNF) plays a key role in the processes of withdrawal and addiction in alcohol use disorder (AUD), and is also involved in liver homeostasis. The role of BDNF in liver damage and its link with liver stiffness are not known. We hypothesize that serum BDNF levels are linked to changes in hepatic elasticity, both of which depend on variations in alcohol consumption. Objectives : We aimed to study the evolution of BDNF levels and changes in the liver stiffness (LS) of AUD subjects, within two months following withdrawal. Methods : We measured LS by FibroScan® (as an indicator of the degree of liver fibrosis), gamma glutamyl transferase (GGT) levels (as a nonspecific but sensitive marker of liver status) and serum BDNF levels of 62 alcohol-dependent subjects without previously identified liver complications. Measures were obtained at the time of withdrawal (M0) and two months later (M2). Results : BDNF levels increased after alcohol withdrawal and small variations of LS were observed. BDNF values increased significantly according to fibrosis stages measured by LS ( p = .028 at M0), and were predicted by GGT levels in a regression model ( p = .007 at M0 and p = .003 at M2). Conclusion : In AUD, BDNF levels were associated with measured LS when divided into fibrosis risk categories. Changes in LS and BDNF levels after alcohol withdrawal may be related to changes in homeostatic mechanisms, in addition to those of liver status.